The ins and outs of fake Indian Jewelry Sorry, you've been taken - Kerman, Henry (The New Mexican, 1974)
Imitation jewelry where it comes from and how to spot.
Master list item #: 8
File location is in the New Mexico file Cabinet
Keywords: Indian Jewelry; Turquoise Jewelry; Fake Jewelry; Indian Art; Arizona; New Mexico; Nevada